Public-Private Earnings Differentials during Economic Transition in Hungary - Jelena Lauésev (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
The paper explores the effect of economic transition on public-private sector pay differential across the pay distribution in Hungary from 1992 until 2003. Over the time period covered by the analysis the public sector had witnessed large-scale privatisations and restructuring through a number of wage reforms. The paper finds that both men and women in the public sector fared significantly worse than their private sector counterparts during 1990s, but this penalty declined to almost zero until 2003. The results from quantile regressions verified that the public sector pay distribution was more compressed than in the private sector and hence workers at and above the median fared significantly worse off having a public sector status even by the end of the period considered. These results are futher reinforced by the method of decomposition of differences in distributions. Moreover, the paper examines public sector pay penalties/premia for different skilled groups of workers. These results show that the public sector within-group earnings equalising effect for male graduates in Hungary was three times greater than the similar estimate reported by studies in developed market economies.
Keywords: J35; J45; 330; wages; public sector; Hungary; Systemtransformation; Lohnstruktur; Vergütungssystem im öffentlichen Dienst; Privatwirtschaft; Schätzung; Ungarn